E-zdey petrol pump payment system via NFC module / Muhammad Faris Izdihar Abdul Aziz - Abdul Aziz, Muhammad Faris Izdihar (2024)
The landscape of petrol payment systems worldwide is undergoing drastically changes, with increasing focus on security, efficiency, and user convenience. The COVID-19 epidemic has created a pressing demand for contactless transactions, which amplifies the obstacles faced by current systems and calls for creative alternatives. This project addresses these issues by introducing an E-zdey Petrol Pump Payment System, leveraging Near Field Communication (NFC) technology and an integrated hardware-software approach. The primary goals of this project are to design a prototype for a contactless fuel pump payment system that incorporates hardware components like the ESP32, PN532 NFC Module, Infrared Sensor, and YF-S401 water sensor, and to develop a mobile application that uses NFC technology to facilitate a safe and seamless fuel pump payments system. The methodology of this project unfolds in two parts including the hardware implementation by involving the assembly of the ESP32-based hardware components, and the development of an Android-based application to complement the system. The seamless interaction between the hardware and the app forms the backbone of this innovative payment system. With the E-zdey application system, users can use their smartphone to make contactless payments using their e-wallet, which also stores all the required data, including balance, transaction history, and payment method layout. Users need to select the value into their E-zdey app and select whether to refuel in Ringgit Malaysia (RM) or Liters. The anticipated benefits of this project extend beyond immediate security and efficiency enhancements. Future recommendations include widespread adoption of NFC-enabled petrol pump systems, contributing to a more secure and streamlined fuel transaction experience.